Study on Lithium-Ion Battery Degradation Caused by Side Reactions in Fast-Charging Process - Gao, Zhenhai; Xie, Haicheng; Yu, Hanqing; Ma, Bin; Liu, Xinhua; Chen, Siyan (Frontiers in Energy Research, 2022)
With the development of electric vehicles, fast-charging is greatly demanded for commercialisation on lithium-ion batteries. The rapid charging process could lead to serious side reactions on the graphite anodes, such as lithium plating and solid electrolyte interface (SEI) film growth, which severely affect the battery performances. However, there is a lack of quantitative research on their contribution ratio to battery performance and the occurrence thresholds. In this work, a P2D model of a lithium-ion battery with the correction of SEI film growth and lithium plating was built. A cyclic charge/discharge experiment was also designed to analyze the changes of SEI film and lithium plating under high charge-rate conditions. It was found that under such conditions, the battery capacity attenuation in the early stage was mainly caused by lithium plating. In the middle and late stages, as the lithium plating tended to be stable, the capacity attenuation was largely caused by the growth of the SEI film. The study provides theoretical support for the improvement of the charge/discharge strategy of lithium-ion batteries.